2012
DOI: 10.3109/07420528.2012.667859
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Melatonin (MT) Signal Facilitates Reentrainment of the Circadian System to Light-Induced Phase Advances by Acting Upon MT2 Receptors

Abstract: The indolamine melatonin is an important rhythmic endocrine signal in the circadian system. Exogenous melatonin can entrain circadian rhythms in physiology and behavior, but the role of endogenous melatonin and the two membrane-bound melatonin receptor types, MT1 and MT2, in reentrainment of daily rhythms to light-induced phase shifts is not understood. The present study analyzed locomotor activity rhythms and clock protein levels in the suprachiasmatic nuclei (SCN) of melatonin-deficient (C57BL/6J) and melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 52 publications
4
60
0
3
Order By: Relevance
“…The SCN has been found to be the main regulator of circadian rhythms, which then sends signals to peripheral cells throughout the body, causing that rhythm to be passed on to the proper cells and tissues (53). However, the SCN can be stimulated by zeitgebers other than light, especially by serotonin and melatonin, although these are thought to be internal feedback regulators as opposed to primary circadian rhythm initiators (112,113,128). Melatonin has also been found to be one of the signaling molecules used by the body to synchronize certain peripheral cells.…”
Section: Circadian Rhythms and Zeitgebers: The Tempo Of Lifementioning
confidence: 99%
“…The SCN has been found to be the main regulator of circadian rhythms, which then sends signals to peripheral cells throughout the body, causing that rhythm to be passed on to the proper cells and tissues (53). However, the SCN can be stimulated by zeitgebers other than light, especially by serotonin and melatonin, although these are thought to be internal feedback regulators as opposed to primary circadian rhythm initiators (112,113,128). Melatonin has also been found to be one of the signaling molecules used by the body to synchronize certain peripheral cells.…”
Section: Circadian Rhythms and Zeitgebers: The Tempo Of Lifementioning
confidence: 99%
“…39 In vitro experiments using ligands toward MLT receptors and SCN slices from wild-type and MLT receptor knockout mice showed that activation of MT 1 receptors inhibited the neuronal firing rate of the SCN, whereas activation of MT 2 receptors phase-shifted circadian rhythms of neuronal firing rates. 26,34,37,40,41 But, in Siberian hamsters in which the MT 1 receptor was functional, but the MT 2 receptor was not, MLT elicited a clear phase shift of the circadian rhythm of SCN electrical activity. 42 In vivo experiments in MLT receptor knockout mice further complicated the scenario.…”
Section: What Are Their Roles?mentioning
confidence: 99%
“…Thus, multiple signaling pathways are mediated by melatonin receptor activation. Focusing on the SCN, both melatonin receptors are involved in regulating the expression of the core clock genes ( Per1 , Per2 , Bmal1 , and Clock ) [26, 36, 37]. Although the circadian machinery is present in every cell, the effect of melatonin on rhythmic clock gene expression is not yet clear.…”
Section: Role Of Melatonin Receptorsmentioning
confidence: 99%